Návrh na zlepšení marketingové strategie firmy - Husáková, Veronika (Vysoké učení technické v Brně. Fakulta podnikatelská, 2012)
Diplomová práce se zabývá marketingovou strategií společnosti prodávající knihy. Teoretická část poskytuje teoretické východiska týkající se marketingové strategie. Na základě analytické části analyzující aktuální marketingovou strategii společnosti jsou vypracovány návrhy na její zlepšení.

Diploma thesis deals with the marketing strategy of a book selling company. Theoretical part provides theoretical background on marketing strategy. Based on analytical part analysing current marketing strategy of the company are developed proposals for its improvement.
Proposal for the Marketing Strategy Improvements of a Company
Keywords: marketingová strategie; marketingový mix; marketingový plán; marketing strategy; marketing mix; marketing plan